Alveolar-cell carcinoma: a problem in sputum cytodiagnosis. Issue 12 (December 1982) - Spriggs, A I; Cole, M; Dunnill, M S
Abstract : Cytology and histology are correlated in a series of 22 cases chosen to illustrate the differential diagnosis between clusters of benign bronchial or bronchiolar cells seen in sputum, and those of alveolar cell carcinoma or adenocarcinoma with alveolar spread. Alveolar-cell carcinoma is characterised by clusters of small epithelial cells in spherical or irregular formations, none showing enough polarity to distinguish a smooth or palisaded surface. The appearances are most distinctive if vacuolation is absent. The diagnosis cannot, however, be confidently made in all cases from morphological features of cells in sputum.